Marketing support of the tourism business - Yakushko, Angelina; Pererva, P. G. (Полтавський державний аграрний університет, 2023)
It has been proven that marketing has long since evolved from a function in an enterprise that was perceived only to create effective advertising and sales promotion. And today it plays an important role primarily in society, namely in building relationships and connections, cultivating values. The relationship between the modern enterprise, partners, customers and employees has become closer: more personalized, more attentive and more aimed at a synergistic effect.
Визначення специфічних чинників готельних послуг
Keywords: marketing; tourism business; partners; customers; synergistic effect